Ex Oriente Luxus. Marco teórico sobre la existencia de una red libre de escala y el uso de superconectores durante el Alto Imperio romano - Pérez González, Jordi (Anabasis. Studia Classica et Orientalia, 2017)
The conquest of the Eastern Mediterranean and the annexation of Egypt under the direct control of Rome gave way to a period of commercial prosperity unprecedented in the history of Rome, where products from all parts of the world could be bought in the taverns of the city. In order to better understand which were producing areas of luxury goods and as it worked its distribution to Rome we have developed a general map of the various routes used by land and sea that formed the intercontinental commercial network during Classical Antiquity. This map will help us better understand what were the major luxury markets under Roman control, what was the role they played in the international network, as they interacted with each other and what were the most important regions within this commercial network.